Atividade radioprotetora, perfil toxicológico e efeito contra a toxicidade da ciclofosfamida do extrato de tucumã: estudos in vitro e in vivo - Guex, Camille Gaube (2020)
Cancer is a multifactorial disease characterized by loss of control of cell division. Nowadays, it is a serious health problem worldwide, leading to many deaths every year. Current treatments for cancer include radiation therapy and chemotherapy, which use ionizing radiation and different drugs to induce cell death, respectively. However, the adverse effects associated with these treatments can become serious and lead to treatment interruption. Natural products are gaining attention to act as alternative therapies to attenuate these effects due to their bioactive compounds. In this scenario, tucumã is an Amazonian fruit with great pharmacological interest due the presence of important bioactive substances, which can act by reducing the damage induced by radiation and chemotherapy. Therefore, we decided to investigate the potential effect of tucumã crude extract (TCE) in mitigating the effects caused by radiation in an in vitro model. Afterward, the acute and repeated dose toxicity of TCE and its activity against the toxicity of cyclophosphamide (CPP) were investigated, all in vivo studies. In addition, we perform the phytochemical characterization of the extract by HPLC-PAD, GC-MS and UHPLC-MS. These analyses revealed the presence of polyphenols, flavonoids, catechins, carotenoids and saturated and unsaturated fatty acids. For the in vitro study, keratinocytes and fibroblasts were treated with TCE (for 24h) and exposed to radiation at a dose of 2 Gy. After 24h, analyses of apoptotic markers and oxidative stress, cell mortality and growth factors were performed. For acute toxicity, female Wistar rats were divided into control and test groups, in which those in the test group were treated with TCE in a single dose of 2000 mg/kg. For the repeated dose toxicity study, male and female rats were used and, except for the control group, were treated with TCE at doses of 200, 400 and 600 mg/kg, orally, for 28 days. Physiological, behavioral, hematological, biochemical and histopathological parameters and markers of oxidative stress were analyzed. For the third study, Wistar rats were used and divided into treatment and pre-treatment. In the treated one, CPP administration preceded oral treatment with TCE; while in pre-treatment, the opposite occurred. CPP was administered (via IP) at a dose of 150 mg/kg (divided into three days) and TCE was administered at doses of 100, 200 and 400 mg/kg, orally, for 14 days. Physiological, hematological and biochemical parameters and markers of oxidative stress were analyzed. Regarding the results of the in vitro study, radiation altered the levels of the apoptotic markers and oxidative stress, as well as of growth factors. The pretreatment with the tucumã extract was able to attenuate the aforementioned parameters, varying according to the cell type. In reference to the acute toxicity study, during the experiment period there were no signs of toxicity nor deaths were recorded. However, when administered repeatedly and at the highest dose (600 mg/kg), renal toxicity was observed in males, as evidenced by histological analysis. In the other parameters, for both males and females, no signs of toxicity were found and no mortality was recorded. Thereby, TCE can be considered safe when administered in low doses. After exposure to CPP, changes in body weights, organs and relative weights were observed. In addition, hematological and biochemical analyses also showed changes, varying for each study. Oral administrations of TCE were not able to significantly attenuate these parameters. However, TCE has improved levels of MDA and carbonylation, as well as SOD activity, all affected by CPP. The pretreatment showed the best results in reducing the toxic effects of CPP, especially in the improvement of oxidative damage markers. Therefore, the results found in this work are promising, indicating that tucumã is a fruit with potential biological activities, however it should be used in low doses.